Zobaczyć więcej świata: polonistyki transatlantyckiej szanse i wyzwania - Siewierski, Henryk (Postscriptum Polonistyczne, 2020)
The author of the article regards the development of Polonistic studies in Brazil in the context of the cultural background of this country, Polish emigration heritage, and the challenges for Polonistics in Latin America. The connections between Polonistics, and comparative and cultural studies are also discussed in the article. The examples of traces of Polish in the canons of foreign literature presented in the article may become a starting point for some to regard from a distance something, which is close, for others to look closely at something, which is far away.